DETERMINANT VARIABLES ON LEVERAGE AND SPEED OF ADJUSTMENT(STUDY IN INDONESIA STOCK EXCHANGE) - Anggun Septina Lukitasari; Tri Gunarsih (MESP–FEB UNS, 2019)
There have been many types of research on capital structure, however, those researches have not shown consistent results yet. This research aims to determine the effect of determinant variables of capital structure on leverage and speed of adjustment partially. The samples comprise 459 manufacturing companies listed in Indonesia Stock Exchange from 2009-2017. The statistic analysis utilized to test the hypothesis is multiple linear regression analysis. The test result shows that the determinant variables of capital structure have significant effects on leverage, and the partial effect of the determinant variables of capital structure (Profitability, Tangibility, Size, Growth Opportunity, and Income Variability) also has a significant effect. For the speed of adjustment, the size variable gives the biggest contribution compared to the other variables.Keywords: Leverage, Speed of Adjustment, Profitability, Tangibility, Size, Growth Opportunity, Income Variability.